2010
DOI: 10.4049/jimmunol.0902640
|View full text |Cite
|
Sign up to set email alerts
|

Secreted IgM Enhances B Cell Receptor Signaling and Promotes Splenic but Impairs Peritoneal B Cell Survival

Abstract: B cell survival has a central role in maintaining immune responses to foreign organisms while curbing autoimmunity. In this study, we show that mature B cell survival is impaired and B cell turnover is accelerated in the spleen of mice lacking secreted IgM. Although in vitro responses to BCR cross-linking were normal, there was a marked reduction in basal ERK and global tyrosine phosphorylation in splenic B cells from serum IgM-deficient mice, suggesting diminished interaction with cognate Ag in vivo. The prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
(60 reference statements)
5
20
0
Order By: Relevance
“…Indeed, B cell subsets in μs−/− mice, including MZ and FO B cells showed enhanced turnover compared to their WT counterparts as measured by enhanced BrDU incorporation (Fig. 5A), as noted by others (48). The turnover-rate of CD21 int CD23− B cells was similar to that of FO B cells in μs−/− mice, but enhanced compared to those in WT mice (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Indeed, B cell subsets in μs−/− mice, including MZ and FO B cells showed enhanced turnover compared to their WT counterparts as measured by enhanced BrDU incorporation (Fig. 5A), as noted by others (48). The turnover-rate of CD21 int CD23− B cells was similar to that of FO B cells in μs−/− mice, but enhanced compared to those in WT mice (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Natural IgM also plays a role in clearing apoptotic cells (87), maintaining B cell homeostasis (88), inflammation (89,90), atherosclerosis (91), and autoimmunity (92,93). Natural IgM was proposed to bind strongly to complement factor C1q and to activate the complement cascade (85,94).…”
Section: Functions Of Natural Igm In Mice: Hints On Linkage Between Imentioning
confidence: 99%
“…Moreover, IgG2a and IgG3 as well as IgA plasma levels are increased in sIgM −/− mice, which also show impaired IgG antibody responses at least to suboptimal doses of a T-cell–dependent antigen. 82–85 Paradoxically, Lewis et al 81 reported decreased IgG2a/c titers against CuOx-LDL in atherosclerotic sIgM −/− Ldlr −/− mice, which may reflect increased immune complex formation with OxLDL in the absence of circulating IgM. Interestingly, infusion of polyclonal IgM into Apoe −/− mice during the last 4 weeks of a 29-week atherogenic diet has been reported to delay lesion formation, whereas infusion of a monoclonal T15id + IgM preparation failed to do so in this setting.…”
Section: Igm: the House Keepermentioning
confidence: 99%